Mutu Bakso Lingkar Kampus Universitas Mataram - Ismatillah, Alifia (Faculty of Agriculture Science & Technology, 2024)
Meatball is a processed food product made from meat which has become one of the favorite menus among students in the vicinity of Universitas Mataram. The aim of this research was to determine the quality of meatballs around the Universitas Mataram campus. The method used in this research was experimental method which conducted in the laboratory using Completely Randomized Design with one factor consisting of meatball vendors around the Universitas Mataram campus i.e. BSL, BCR, BRJ, BMA, BPJ and BJG with three trials, resulting in 18 experimental units. The parameters observed were moisture content, protein content, borax, total microbes, total coliforms, and meatball sensory properties. The data obtained were analyzed with a 5 % of significance level using CoStat software and followed by Honestly Significant Difference test for parameters showing significant differences. The results showed that meatballs sold by vendors around the Universitas Mataram campus have significant differences in moisture content, flavor, and texture (scoring test), but have no significant differences in protein content, color, taste, and texture (hedonic test). The meatballs meets the Indonesian National Standard (SNI) for the protein content, and do not contain borax. However, microbial quality of the meatballs does not meet yet SNI 01-3818-2014 except for Mr. Jhon Meatball.